Bibliometric Analysis of Postgraduate Theses on Sport Management - Çakir, Ferhat (Indonesian Journal of Sport Management, 2024)
This research aims to carry out a bibliometric analysis of postgraduate theses in sports management. Bibliometric analysis methods are used to identify trends, patterns and conclusions that emerge from the collection of theses that have been researched. Bibliometric data such as keyword frequency, thesis length and topic distribution will be explored to understand the development and focus of research in sports management. The findings from this research will provide in-depth insight into recent developments in postgraduate research in sports management and provide directions for future research in this discipline.